2020
DOI: 10.30773/pi.2019.0216
|View full text |Cite
|
Sign up to set email alerts
|

Time to Take Sleeping Pills and Subjective Satisfaction among Cancer Patients

Abstract: Objective We investigated the influence of the time to take hypnotics and daytime activity on patient satisfaction with sleeping pills.Methods Ninety-six cancer patients who were currently taking benzodiazepine or z-drug as hypnotics were grouped into satisfied and dissatisfied groups. The subjects’ symptoms, time to take sleeping pills, bedtime, sleep onset time, wake up time, and time in bed within 24 hours (TIB/d) were obtained.Results The satisfied group had significantly late sleeping pill ingestion time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Additionally, we proposed to advise patients to take sleeping pills approximately 7 h before their usual getting- out-of-bed time, not 30 min before bedtime, which can lead to confusion regarding the time the pills must be taken for patients to induce short sleep latency. Among cancer patients [ 29 ], we reported that reducing the duration from the sleeping pill ingestion to wake-up time can influence the satisfaction of sleeping pills. Furthermore, we proposed using the sleep in- dex time in bed during a day (TIB/d) as the total TIB during 24 h. This concept is also similar to the concept of DBST in terms of a homeostatic drive (Process S).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we proposed to advise patients to take sleeping pills approximately 7 h before their usual getting- out-of-bed time, not 30 min before bedtime, which can lead to confusion regarding the time the pills must be taken for patients to induce short sleep latency. Among cancer patients [ 29 ], we reported that reducing the duration from the sleeping pill ingestion to wake-up time can influence the satisfaction of sleeping pills. Furthermore, we proposed using the sleep in- dex time in bed during a day (TIB/d) as the total TIB during 24 h. This concept is also similar to the concept of DBST in terms of a homeostatic drive (Process S).…”
Section: Discussionmentioning
confidence: 99%
“…The DBS-2 scale was derived from the C-DBS scale which was developed to briefly measure cancer-related dysfunctional beliefs about sleep. The C-DBS scale has already been successfully applied to numerous studies on sleep problems of cancer patients [10][11][12]. While applying digital CBT-I using digital therapeutic application to patients with insomnia, brief measure tools are needed to assess insomnia-related symptoms or psychological problems such as depression, anxiety, insomnia severity, and dysfunctional beliefs about sleep.…”
Section: Discussionmentioning
confidence: 99%
“…It can measure cancer patients' dysfunctional beliefs about sleep. The C-DBS has been successfully applied in previous numerous studies [7][8][9][10][11][12]. It this study, we examined the validity and reliability of a Dysfunctional Beliefs about Sleep-2 items (DBS-2) scale, which was adapted from the C-DBS scale, using two sample groups (a general population and a clinical sample of subjects with insomnia disorder) to explore whether it could be applied as an ultra-brief rating scale for evaluating dysfunctional beliefs about sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Any answers of 15 min (one quarter of an hour) were converted to 0.25 (one quarter) and 30 min (half an hour) were converted to 0.50. In this manner, 22:45 was transformed into 10.75 [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%